A semi-metallic Co 2 Preparation method of MnGa thermoelectric material

The preparation of Co2MnGa material is simplified by the two-step chemical reaction method, and the temperature unevenness and oxidation problems of traditional arc smelting methods are solved, and the composition uniformity and thermoelectric performance of the material are improved, which is suitable for promotion and application.

CN117926099BActive Publication Date: 2024-12-17WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311804498.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2024-12-17
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

The traditional arc smelting preparation of Co2MnGa materials has problems such as uneven temperature, high equipment requirements, large energy consumption and easy oxidation of materials, which limits the low cost and high-quality preparation of materials.

Method used

The two-step chemical reaction method is used to form Mn-Ga alloy through liquid solid phase reaction, and then mixed with Co powder for solid phase reaction and discharge plasma sintering, simplifying the preparation process, reducing temperature and equipment requirements, and avoiding oxidation.

Benefits of technology

The composition uniformity and thermoelectric performance of Co2MnGa material have been improved, the Seebeck coefficient reaches -29uV·K-1, and the Nernst coefficient reaches 7.6uV·K-1 at room temperature, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004629868930000011
    Figure HDA0004629868930000011
  • Figure HDA0004629868930000012
    Figure HDA0004629868930000012
  • Figure HDA0004629868930000021
    Figure HDA0004629868930000021
Patent Text Reader

Abstract

The invention discloses a method for preparing a semi-metallic Co2MnGa thermoelectric material. First, Mn powder and Ga block are weighed according to a ratio, mixed, vacuum-sealed, heated for liquid-solid phase reaction to form a Mn-Ga alloy; then the obtained Mn-Ga alloy is ground into powder, Co powder is added in proportion to mix evenly, and pressed into a block; the obtained block is vacuum-sealed, heated for solid phase reaction, quenched and cooled; ground into powder, and discharge plasma sintering is performed to obtain a Co2MnGa block thermoelectric material. The semi-metallic Co2MnGa thermoelectric material of the present invention uses Mn powder, Ga block and Co powder as main raw materials, adopts step-by-step mixing, step-by-step reaction and discharge plasma sintering mechanism, can effectively improve the problems of Mn and Ga oxidation on the basis of simplifying the preparation process, ensure the composition uniformity of the obtained composite material, and at the same time is conducive to further improving the thermoelectric performance of the obtained Co2MnGa material, which is suitable for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoelectric materials, and in particular relates to a method for preparing a semi-metallic Co2MnGa thermoelectric material. Background Art

[0002] As an environmentally friendly new energy material, thermoelectric materials can realize direct conversion between thermal energy and electrical energy. Thermoelectric devices composed of thermoelectric materials have the advantages of small size, fast startup, no moving parts, and long service life. They have broad application prospects in aerospace, automobile exhaust recovery, industrial waste heat power generation, thermoelectric refrigerators, automobile seat cooling and chip cooling.

[0003] In the past few decades, many good longitudinal thermoelectric materials have been proved to be topological insulators. Recently, with the emergence of topological semimetals, the Nernst effect and anomalous Nernst effect have attracted more and more attention in transverse thermoelectric applications. Due to the large Bell curvature near the Fermi energy, large anomalous Nernst effect thermal power is achieved in some topological ferromagnets, which shows great potential in stable and precise temperature control, especially in the field of micron or nanometer size devices. For example, the anomalous Nernst coefficient of topological semimetal materials such as Co3Sn2S2, Co2MnGa and Fe3Ga is 3~8uV·K -1 , the anomalous Hall conductivity is 0.5~5A·m -1 ·K -1 . Co2MnGa has a higher anomalous Nernst coefficient at room temperature and has broad application prospects.

[0004] However, the traditional method for preparing Co2MnGa materials is to use arc melting combined with vacuum melting technology; the specific process includes: first using arc melting method to prepare ingots, and then placing them in a high vacuum melting furnace for melting to obtain Co2MnGa materials. Among them, arc melting uses the high temperature released by the arc to melt metal materials, which has problems such as excessive temperature, uneven temperature and uncontrollable temperature, which can easily cause Mn and Ga melts to splash; during vacuum melting, the temperature in the furnace needs to reach above 1200°C, and the prepared materials are easily oxidized. The use of arc melting combined with vacuum melting technology has high equipment requirements and high energy consumption. The prepared materials are prone to Mn and Ga oxidation, which seriously limits the low-cost and high-quality preparation of Co2MnGa materials, and is not conducive to further composition regulation and thermoelectric performance optimization. Therefore, it is very important to further develop a simple and efficient preparation method with a stable and controllable synthesis process. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for preparing a semi-metallic Co2MnGa thermoelectric material in view of the problems and shortcomings of the existing arc melting preparation technology. On the basis of simplifying the preparation process, it can effectively improve the problems such as Mn and Ga oxidation, ensure the composition uniformity of the obtained thermoelectric material, and at the same time be conducive to further improving the thermoelectric performance of the obtained Co2MnGa material, which is suitable for promotion and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a semi-metallic Co2MnGa thermoelectric material comprises the following steps:

[0008] 1) Weigh Mn powder and Ga block according to the ratio; mix and seal in vacuum, add into a muffle furnace, heat and react with liquid-solid phase to form Mn-Ga alloy;

[0009] 2) Grinding the obtained Mn-Ga alloy into powder, adding Co powder according to the stoichiometric ratio of Co2MnGa, mixing evenly, and pressing into a block;

[0010] 3) vacuum-seal the obtained block, place it in the muffle furnace again, heat it for solid phase reaction, and quench and cool it;

[0011] 4) Grinding the quenched bulk product into powder and performing discharge plasma sintering to obtain a semi-metallic Co2MnGa thermoelectric bulk material.

[0012] In the above scheme, the molar ratio of the Mn powder, Ga block and Co powder is 1-1.05:1-1.02:2.

[0013] In the above scheme, the particle size of the Mn powder is 50-2000 mesh; the particle size of the Ga block is 0.1-5 mm; and the particle size of the Co powder is 50-2000 mesh.

[0014] In the above scheme, the vacuum degree of the vacuum seal is 10 -2 Below Pa.

[0015] In the above scheme, the temperature rise rate used in the liquid-solid phase reaction step in step 1) is 1-10°C·min -1 , the reaction temperature is 500-900°C, and the insulation time is 30-240min.

[0016] In the above scheme, the pressure used in the pressing step is 50-100 MPa, and the pressure holding time is greater than 3 minutes.

[0017] Furthermore, the compression step uses a tablet press.

[0018] In the above scheme, the heating rate used in the solid phase reaction in step 3) is 1-10°C·min-1 The sintering temperature is 800-1200℃ and the holding time is greater than 6h.

[0019] Preferably, the sintering temperature of the solid phase reaction is 800-1000° C., and the sintering time is 12-24 hours.

[0020] Furthermore, the sintering temperature of the solid phase reaction is higher than that of the liquid-solid phase reaction.

[0021] In the above scheme, the quenched block must pass through a sieve of not less than 120 mesh after grinding.

[0022] In the above scheme, the heating rate adopted in the spark plasma sintering step is 20-100°C·min -1 , the sintering temperature is 700-900°C, the holding time is not less than 5 minutes, the sintering pressure is 50-200 MPa, and the cavity vacuum is below 10 Pa. The spark plasma sintering process adopted by the present invention can further promote the continued reaction of a small amount of incompletely reacted parts in the secondary solid phase reaction during the densification process, thereby promoting the acquisition of a densified single-phase product.

[0023] The semi-metallic Co2MnGa thermoelectric material of the present invention uses Mn powder, Ga blocks and Co powder as main raw materials, adopts step-by-step mixing, step-by-step reaction and discharge plasma sintering mechanism, and can effectively ensure the chemical composition and thermoelectric performance of the Co2MnGa thermoelectric material on the basis of improving the preparation efficiency: first, in view of the problems that the saturated vapor pressure of Mn and Ga is high and splashing and volatilization are easy to occur during the synthesis process, the Mn powder and Ga blocks are subjected to liquid-solid phase reaction to synthesize a stable Mn-Ga alloy, which can more accurately ensure the stoichiometric ratio of the material; second, it effectively improves the problems that the chemical properties of Co, Mn and Ga in the raw materials are quite different, and when they are synthesized together, it is easy to cause element diffusion differentiation and uneven distribution of chemical components; third, in view of the problem that Mn and Ga are easily oxidized, the two are first synthesized into a Mn-Ga alloy with more stable chemical properties, which can minimize the degree of oxidation.

[0024] It should be noted that, in order to solve the oxidation problem, the Mn powder and Ga block need to be quickly vacuum-sealed after weighing to avoid long-term exposure to the atmosphere. In order to solve the problem of component uniformity, on the one hand, the crushed Mn-Ga alloy needs to be mixed and ground evenly with the Co powder to reduce the agglomeration of the powder; on the other hand, the powder needs to be pressed into a block before the solid phase reaction to promote the uniform diffusion of the elements during the reaction.

[0025] The Co2MnGa bulk material prepared according to the above scheme has a negative Seebeck coefficient in the range of 300-500K, and its absolute value increases with increasing temperature. The maximum Seebeck coefficient at 300K is -29uV·K -1The Hall conductivity in the range of 300-480K increases rapidly with the increase of magnetic field, and then gradually reaches saturation. The Hall conductivity at 300K is 500-550S·cm -1 (Abnormal Hall conductivity is 500~520S·cm -1 ); The Nernst coefficient at room temperature increases with the increase of the magnetic field. When the magnetic field is 0.5T, the Nernst coefficient of the sample can reach 6.8~7.6uV·K -1 .

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1) The preparation process of the semi-metallic Co2MnGa of the present invention adopts a two-step chemical reaction method, avoids the use of complex preparation processes such as arc melting combined with high-temperature melting, has low requirements on reaction equipment, involves a short preparation cycle and a low temperature (which can be controlled to be below 1000°C), can effectively simplify the preparation process, and is suitable for promotion and application.

[0028] 2) The Co2MnGa material prepared by the present invention has uniform composition and controllable components, which can effectively improve the problems of Mn and Ga oxidation that are prone to occur during the material preparation process, greatly improve the preparation efficiency, and help improve the thermoelectric properties of the obtained Co2MnGa material. Its Seebeck coefficient can reach -29uV·K at room temperature. -1 The Nernst coefficient can be as high as 7.6uV·K at room temperature (300K). -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD spectra of Co2MnGa materials prepared in Examples 1 and 2 and the comparative example.

[0030] Figure 2 The SEM photos of Co2MnGa materials prepared in (a) Example 1, (b) Example 2, and (c) Comparative Example are respectively shown.

[0031] Figure 3 The curves of Seebeck coefficient of Co2MnGa materials obtained in Examples 1 and 2 and the comparative example varying with temperature in the range of 300 to 500K.

[0032] Figure 4 The graphs show the change of the anomalous Hall conductivity of the Co2MnGa samples obtained in Examples 1 and 2 and the comparative example with the magnetic field in the range of 300 to 480K.

[0033] Figure 5 3 is a curve showing the variation of the Nernst coefficient of the Co2MnGa samples obtained in Examples 1 and 2 and the comparative example with the magnetic field at room temperature. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through a specific implementation case. This implementation case is specifically implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given, but the scope of protection of the present invention is not limited to the implementation case given below.

[0035] In the following examples and comparative examples, the particle size of the Mn powder used is 200 mesh, the particle size of the Ga block powder is 0.1-5 mm, and the particle size of the Co powder is 300 mesh.

[0036] Example 1

[0037] A method for preparing a semi-metallic Co2MnGa thermoelectric material comprises the following steps:

[0038] 1) Mix Mn powder and Ga block in equal molar ratio (total 10g) and seal in vacuum to ensure vacuum degree reaches 10 - 2 Pa, and then placed in a muffle furnace at 5℃·min -1 The temperature was raised to 800°C at a rate of 1.5°C and kept at this temperature for 180 minutes to form a Mn-Ga alloy with more stable chemical properties.

[0039] 2) Grind the obtained Mn-Ga alloy product into powder, add Co powder according to the stoichiometric ratio of Co2MnGa and mix well, and press into blocks using a tablet press at a pressure of 50MPa and a holding time of 5min;

[0040] 3) The obtained block was vacuum sealed and placed in a muffle furnace again at 2°C min -1 The temperature was raised to 1000°C at a rate of 1.5°C and kept at this temperature for 24 hours; then the mixture was quenched and cooled;

[0041] 4) Grind the product obtained in step 3) and pass it through a 120-mesh screen, then sinter it in a spark plasma sintering furnace at a heating rate of 100°C·min -1 The sintering temperature is 800℃, the holding time is 5min, the sintering pressure is 50MPa, and the cavity vacuum is 10Pa to obtain a dense semi-metallic Co2MnGa thermoelectric material.

[0042] The XRD and SEM test results of the product obtained in this example are shown in Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that the obtained sample is composed of a single Co2MnGa phase (consistent with the standard card). Figure 2 The SEM results show that the obtained sample has uniform composition and high density, and is a Co2MnGa single-phase structure. The few black contrasts in the image are sample holes.

[0043] The curve of Seebeck coefficient of Co2MnGa material obtained in this embodiment changing with temperature is shown in FIG. Figure 3 As shown in the figure, the Seebeck coefficient of the sample is negative, and its absolute value increases with increasing temperature. The Seebeck coefficient at 300K is about -28.3uV·K -1 Compared with the reported literature, the value of the sample synthesized in this embodiment is increased by about 8%. The Hall conductivity curve of the Co2MnGa sample obtained in this embodiment in the range of 300-480K with magnetic field is shown in Figure 4 The Hall conductivity of the Co2MnGa sample increases rapidly with the increase of the magnetic field, and then gradually reaches saturation. It has a large anomalous Hall effect at 300K, and the anomalous Hall conductivity reaches 520S·cm -1 When the magnetic field is 0.5T, the Nernst coefficient of the obtained sample is about 7.6uV·K -1 , reaching the level of single crystal samples.

[0044] Example 2

[0045] A method for preparing a semi-metallic Co2MnGa thermoelectric material comprises the following operations:

[0046] 1) Mix Mn powder and Ga block in a molar ratio of 1.05:1 (a total of 20 g) and vacuum seal to ensure that the maximum vacuum degree reaches 10 -2 Pa, and then placed in a muffle furnace at 5℃·min -1 The temperature was raised to 850°C at a rate of 1.5°C and kept at this temperature for 240 minutes to form a Mn-Ga alloy with more stable chemical properties.

[0047] 2) Grind the obtained Mn-Ga alloy product into powder, add Co powder according to the stoichiometric ratio of Co2MnGa and mix well, and press into blocks using a tablet press at a pressure of 50MPa and a holding time of 5min;

[0048] 3) The obtained block was vacuum sealed and placed in a muffle furnace again at 2°C min -1 The temperature was raised to 1000°C at a rate of 1000°C and kept at this temperature for 12 hours; then the mixture was quenched and cooled;

[0049] 4) Grind the product obtained in step 3) and pass it through a 120-mesh screen, then sinter it in a spark plasma sintering furnace at a heating rate of 80°C·min -1 , the sintering temperature is 850℃, the holding time is 5min, the sintering pressure is 40MPa, the cavity vacuum is 10Pa, and finally a dense semi-metallic Co2MnGa thermoelectric material is obtained.

[0050] The XRD and SEM test results of the product obtained in this example are shown in Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that the obtained sample is composed of a single Co2MnGa phase (consistent with the standard card). Figure 2 The SEM results show that the obtained sample has uniform composition and high density, and is a Co2MnGa single-phase structure. The few black contrasts in the image are sample holes.

[0051] Thermoelectric properties measurement ( Figures 3 to 5 ) shows that the Seebeck coefficient of the obtained sample at 300K is about -29.0uV·K -1 , has a large anomalous Hall effect at 300K, and the anomalous Hall conductivity reaches 500S·cm -1 When the magnetic field is 0.5T, the Nernst coefficient of the obtained sample is about 6.8uV·K -1 , reaching the level of single crystal samples.

[0052] Comparative Example

[0053] A one-step method for directly preparing Co2MnGa thermoelectric material comprises the following steps:

[0054] 1) Mix Co powder, Mn powder and Ga block in a molar ratio of 2:1:1 (total 10g) and vacuum seal to ensure the maximum vacuum degree reaches 10 -2 Pa, and then placed in a muffle furnace at 2 °C min -1 The temperature was raised to 1000°C at a rate of 1.5°C and kept at this temperature for 24 hours; then the mixture was quenched and cooled;

[0055] 2) The obtained product was ground and passed through a 120-mesh screen, and then sintered in a spark plasma sintering furnace at a heating rate of 100°C min -1 , the sintering temperature is 800℃, the holding time is 5min, the sintering pressure is 50MPa, the cavity vacuum is 10Pa, and finally the semi-metallic Co2MnGa thermoelectric material is obtained.

[0056] Figure 1 XRD analysis showed that the sample was composed of Co2MnGa phase. Figure 2 The SEM images show that the sample composition is complex and there are multiple phase contrasts. Combined with the energy spectrum analysis, it is found that the gray contrast is the Co2MnGa phase that deviates from the stoichiometric ratio, the white contrast is the Ga-rich phase, the gray-white contrast is the Co-rich phase, and the black contrast is the MnO phase. Thermoelectric property measurement ( Figures 3 to 5 ) shows that the Seebeck coefficient of the obtained sample at 300K is only -17.4uV·K -1 , the anomalous Hall conductivity at 300K is 430S·cm-1 When the magnetic field is 0.5T, the Nernst coefficient of the obtained sample is about 4.9uV·K -1 ; Poor thermoelectric performance.

[0057] In addition, it should be further pointed out that, using the above-mentioned preparation method of the comparative example, further extending the insulation reaction time of step 1) or increasing the insulation reaction temperature cannot achieve obvious performance improvement effect.

[0058] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing a semi-metallic Co2MnGa thermoelectric material, characterized in that: The steps include: 1) weighing Mn powder and Ga block according to the ratio; mixing, vacuum sealing, heating for liquid-solid phase reaction, and forming Mn-Ga alloy; the liquid-solid phase reaction temperature is 500-900° C., and the holding time is 30-240 min; 2) Grinding the obtained Mn-Ga alloy into powder, adding Co powder according to the stoichiometric ratio of Co2MnGa, mixing evenly, and pressing into a block; 3) vacuum sealing the obtained block, heating it for solid phase reaction, and quenching and cooling it; the sintering temperature used in the solid phase reaction is 800-1200° C., and the holding time is greater than 6 hours; 4) Grind the quenched bulk product into powder and perform discharge plasma sintering to obtain a semi-metallic Co2MnGa thermoelectric bulk material; at room temperature, when the magnetic field is 0.5T, the Nernst coefficient can reach 6.8 to 7.6uV·K -1 .

2. The preparation method according to claim 1, characterized in that: The molar ratio of the Mn powder, Ga block and Co powder is 1-1.05:1-1.02:

2.

3. The preparation method according to claim 1, characterized in that: The particle size of the Mn powder is 50-2000 mesh; the particle size of the Ga block is 0.1-5 mm; and the particle size of the Co powder is 50-2000 mesh.

4. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum seal is 10 -2 Below Pa.

5. The preparation method according to claim 1, characterized in that: The temperature rise rate used in the liquid-solid phase reaction step in step 1) is 1-10°C·min -1 .

6. The preparation method according to claim 1, characterized in that: The pressure used in the pressing step is 50-100 MPa, and the pressure holding time is greater than 3 minutes.

7. The preparation method according to claim 1, characterized in that: The solid phase reaction in step 3) is heated at a rate of 1 to 10°C min -1 .

8. The preparation method according to claim 1, characterized in that: The block obtained after quenching is ground and passed through a sieve of not less than 120 mesh.

9. The preparation method according to claim 1, characterized in that: The heating rate used in the spark plasma sintering step is 20-100°C·min -1 The sintering temperature is 700-900°C, the holding time is not less than 5 minutes, the sintering pressure is 50-200MPa, and the cavity vacuum is below 10Pa.

10. A semi-metallic Co2MnGa thermoelectric material prepared according to the preparation method according to any one of claims 1 to 9.